Common and Idiosyncratic Components in Real Output : Further International Evidence - Nadal De Simone, Francisco (IMF Working Papers; Working Paper ;, 2002)
This paper uses the classical (level) definition of business cycles to analyze the characteristics-duration, amplitude, steepness, and cumulative output movements-of the real GDP series of France, Germany, Italy, the rest of the euro area, and the United States. An index of concordance and its test statistic suggest a great deal of comovement/synchronization between output cycles. Following that result, a dynamic factor model is estimated. Output fluctuations are mostly explained by a global common component and an euro area common component. However, idiosyncratic components also matter, especially for France, the rest of the euro area, and the United States.